CRP Livestock Vietnam Priority Country - RHoMIS Baseline Survey - Hammond, James; Mai Tu; Teufel, Nils; Wijk, Mark T. van; Douxchamps, Sabine (International Livestock Research Institute, 2023)
A characterisation and baseline survey of smallholder farmers undertaken at the start of the Livestock CRP Vietnam Priority Country project.